Isolation and Characterization of Gram-Negative Bacterial Species from Pasteurized Dairy Products: Potential Risk to Consumer Health - Solomon H. Mariam (Journal of Food Quality)
Pathogenic bacterial contaminants of dairy products cause economic and human life losses if not destroyed by pasteurization. Gram-negative bacteria are among such major contaminants. Contamination persists because of faulty pasteurization or occurs during postpasteurization processing. Many factors, including presence of asymptomatic healthy carriers, existence of broad-range host pathogens, and resistance of pathogens to ordinary disinfectants, hamper the control of such pathogens. Here, samples of pasteurized dairy products were subjected to enrichment/selective cultures to test for possible Salmonella contamination, followed by growth on/in various media to test for phenotypic properties and some virulence characteristics of isolates (catalase, urease, oxidase, gelatinase, etc.). Isolates were characterized by phenotypic and genotypic tests for identification and resistance to clinically relevant antibiotics, including disk diffusion and for β-lactamase production. All milk samples harbored Gram-negative bacilli, which constitute a public health hazard. All of the isolates exhibited intermediate-level or higher resistance to ≥2 clinically relevant antibiotics, while some were susceptible. None tested positive for phenotypic gelatin hydrolysis but exhibited alpha- or beta-hemolysis. Sequence alignments of 16S rRNA gene partial sequences suggested up to 99% sequence similarities to subspecies of Salmonella enterica. Most isolates were also β-lactamase producers, especially blaTEM. In conclusion, high contamination rates were found in all Ethiopian pasteurized milk samples. The reasons for this burden of contamination need to be elucidated for meaningful and targeted control. Larger studies are needed, specifically to reveal points of entry of potential pathogens into dairy products. Information from this work will help to address and control previously unrecognized health hazards associated with consumption of pasteurized dairy products.